Hepatoprotective activity of Averrhoa bilimbi L. fruit extract on carbon tetrachloride-induced acute liver faiure in Wistar rats - Rachellicya Ristioni Sihaloho; Chodijah Chodijah; Joko Wahyu Wibowo; Siti Thomas Zulaikhah; Nurul Hidayah; Shabrina Syifa Ghaissani; Mohammad Ariq Nazar; Titiek Sumarawati; Agung Putra (Universa Medicina, 2023)
Background Acute liver failure (ALF) is a state of rapid and progressive deterioration of liver function. Continuous exposure to chemicals and viruses can increase reactive oxygen species (ROS) which leads to prolonged inflammation due to the production of tumor necrosis factor-alpha (TNF-á) thus inhibiting the production of platelet-derived growth factor (PDGF). The objective of this study was to evaluate the effect of administration of Averrhoa bilimbi L. fruit extract on PDGF levels and TNF-á levels in carbon tetrachloride (CCl4)-induced ALF rats. MethodsThis study used a post-test-only control group design involving 20 Wistar rats. They were randomized into 4 groups, namely sham, control, T1, and T2. Group T1 was exposed to CCl4 with the administration of A. bilimbi fruit extract at a dose of 500mg/kgBW, while, group T2 was exposed to CCl4 and given A. bilimbi fruit extract of 750 mg/kgBW. On the 15th day, the serum was analyzed to determine the levels of PDGF and TNF-á using ELISA. ResultsThe highest mean PDGF level in the control group was 146.60±15.36 pg/mL, while the highest mean TNF-á level in group T1 was 40.11±4.44 pg/mL. The One-way ANOVA test showed that there were significant differences in TNF-á (p=0.002) and PDGF (p=0.000) levels between the study groups. ConclusionThe administration of A.bilimbi L. fruit extract affected PDGF and TNF-á levels in CCl4-induced ALF rats. The present study revealed that A. bilimbi fruits have significant hepatoprotective activity in experimental Wistar rats.